Haploinsufficiency of PRR12 causes a spectrum of neurodevelopmental, eye, and multisystem abnormalities - Chowdhury, Fuad; Wang, Lei; Al-Raqad, Mohammed; Amor, David J.; Baxová, Alice; Bendová, Šárka; Biamino, Elisa; Brusco, Alfredo; Caluseriu, Oana; Cox, Nancy J.; Froukh, Tawfiq; Gunay-Aygun, Meral; et al. (Genetics in Medicine, 2021)
Purpose: Proline Rich 12 (PRR12) is a gene of unknown function with suspected DNA-binding activity, expressed in developing mice and human brains. Predicted loss-of-function variants in this gene are extremely rare, indicating high intolerance of haploinsufficiency. Methods: Three individuals with intellectual disability and iris anomalies and truncating de novo PRR12 variants were described previously. We add 21 individuals with similar PRR12 variants identified via matchmaking platforms, bringing the total number to 24. Results: We observed 12 frameshift, 6 nonsense, 1 splice-site, and 2 missense variants and one patient with a gross deletion involving PRR12. Three individuals had additional genetic findings, possibly confounding the phenotype. All patients had developmental impairment. Variable structural eye defects were observed in 12/24 individuals (50%) including anophthalmia, microphthalmia, colobomas, optic nerve and iris abnormalities. Additional common features included hypotonia (61%), heart defects (52%), growth failure (54%), and kidney anomalies (35%). PrediXcan analysis showed that phecodes most strongly associated with reduced predicted PRR12 expression were enriched for eye- (7/30) and kidney- (4/30) phenotypes, such as wet macular degeneration and chronic kidney disease. Conclusion: These findings support PRR12 haploinsufficiency as a cause for a novel disorder with a wide clinical spectrum marked chiefly by neurodevelopmental and eye abnormalities.
CRIS-Team Scopus Importer:2021-04-16